Heterogeneity in Returns to Work Experience: A Dynamic Model of Female Labor Force Participation - YAMADA, Ken (Institutional Knowledge at Singapore Management University, 2009)
This paper provides structural estimates of heterogeneous returns to work experience for Japanese married women. A dynamic model of labor force participation is used to account for dynamic selfselection into employment. Heterogeneity is incorporated into the model in a way that allows for the multidimensional skill heterogeneity in employment and home production and for the individual-specific slope and curvature of experience effect on earnings. The structural estimates and their comparison to the reduced-form estimates highlight the importance of dynamic self-selection into employment and heterogeneity in returns to work experience.